Empowering People with Mental Disorders through Mushroom Home Kits: A Social Entrepreneurship Approach for Economic Independence - Cahyati Teguh Pancani, Peni; Hartono, Dudi; Putra Giandah, Satrio; Agustina, Sonia; Ikrami Dwi Putri, Rara (Yayasan Rumah Ilmu Professor, 2025)
People with mental disorders (ODGJ) often face significant stigma and limited access to economic opportunities, hindering their journey toward independence. This community-based research introduces a novel entrepreneurial model: marketing mushroom home kits explicitly designed for ODGJ. The initiative combines therapy with practical skill development by enabling participants to cultivate oyster mushrooms at home using simple tools and guided instructions. Through participatory methods, including training, mentoring, and family involvement, the project demonstrates positive psychological impacts such as improved confidence and sense of responsibility alongside tangible economic benefits. Results indicate strong market potential for mushroom-based products and enthusiastic reception from families and local communities. Despite challenges like limited technical understanding and digital access, the program shows promise in reducing social stigma and fostering sustainable micro-businesses. This study highlights the value of inclusive, low-cost entrepreneurship models that integrate mental health rehabilitation with income-generating activities, offering a replicable framework for empowering vulnerable groups.